2021
DOI: 10.21203/rs.3.rs-524148/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microbial Community Structure Drives Predatory Myxobacteria Distribution Under Different Compost Manures

Abstract: Myxobacteria are unique predatory microorganisms with a distinct social lifestyle. The associated taxa play key roles in the microbial food webs in different ecosystems and regulate the community structures of soil microbial communities. Compared with conditions under conventional management, under organic conditions, myxobacteria abundance increases in the soil, which could be related to the presence of abundant myxobacteria in the applied compost manure. In the present study, high-throughput sequencing techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Myxococcales are highly abundant in Arctic soils (Malard and Pearce, 2018), and have been observed at this study site before (Scheel et al, 2022). Bacterial predators and particularly Myxococcales may play key roles in microbial food webs, as recently demonstrated (Dai et al, 2021; Petters et al, 2021). Within the active layer, seasonal prokaryotic blooms support higher prey and predator abundance and we hypothesize that the formation of spore-containing fruiting bodies in Myxococcales (Huntley et al, 2011) offers resistance to the winter freeze-off.…”
Section: Discussionmentioning
confidence: 77%
“…Myxococcales are highly abundant in Arctic soils (Malard and Pearce, 2018), and have been observed at this study site before (Scheel et al, 2022). Bacterial predators and particularly Myxococcales may play key roles in microbial food webs, as recently demonstrated (Dai et al, 2021; Petters et al, 2021). Within the active layer, seasonal prokaryotic blooms support higher prey and predator abundance and we hypothesize that the formation of spore-containing fruiting bodies in Myxococcales (Huntley et al, 2011) offers resistance to the winter freeze-off.…”
Section: Discussionmentioning
confidence: 77%
“…Because of their lytic capacity, Myxobacteria are considered as an important micropredators playing a key role in structuring and regulating soil microbial communities (Shimkets et al, 2006;Phillips et al, 2022). The presence of this taxon was strongly influenced by bacterial communities and was previously reported to be significantly positively correlated to alpha diversity indices of Chao1 and Observed OTU (Dai et al, 2021) and of ACE, Shannon and Simpson (Wang et al, 2020). Thus, in our study the higher alpha diversity indices (observed ASV, Chao1 and Shannon) may have promoted the occurrence of the Myxobacteria in farms P and F by given them a broader choice of potential prey microorganisms.…”
Section: Discussionmentioning
confidence: 97%
“…These same members of Bacteroidetes and Alphaproteobacteria responded positively to the application of calcium silicate (wollastonite) to forest soils in New Hampshire, which had a slight opposite effect on soil pH compared to liming (Sridevi et al, 2012). Liming produced an increase in the same groups of surface‐colonizing bacteria in agricultural soils (Xun et al, 2016) and sewage (Wan et al, 2015), while manure with higher calcium content also heavily favoured Haliangiaceae (Dai et al, 2021). In addition to directly promoting bacterial growth and adherence, soil calcium can promote the sorption of organic matter to mineral surfaces via cation bridging (Römkens et al, 1996; Rowley et al, 2018) which may increase resource availability for surface‐colonizing bacteria.…”
Section: Discussionmentioning
confidence: 99%